Identifikace strevních baktérií systémy ENTEROtest 1 a 2 a ENTERO-Rapid - Sedlácek, I; Pakrová, E (Ceskoslovenska epidemiologie, mikrobiologie, imunologie, 1992)
The identification efficacy of two systems, ENTEROtest 1 & 2 and ENTERO-Rapid (fy. Lachema a. c., Brno), was compared. A total 123 well known strains of enteric bacteria were tested. The ENTEROtest 1 & 2 system correctly identified 87.0% tested strains to the species level, the ENTERO-Rapid system correctly identified 76.4% of these strains.
Keywords: bakteriologické techniky; Bacteriological Techniques; Enterobacteriaceae